Pendampingan Proses Penyembelihan dan Pendistibusian Hewan Qurban di Kampus Universitas WR Supratman Surabaya - Gamal, Ahmad; PurwokoFakultas Ekonomi dan Bisnis Universitas WR Supratman Surabaya, Bambang; Kartika, Mira Gayatri; Wirawan, Desak Gede Tiara Sharasshita; Hidyantari, Erlyna; Prihartanti, Wiwik; Suasridewi, Desak Gede; Rahmanto, Agus; H, Hardiono (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The purpose of this community service is to provide assistance in managing the implementation of welcoming the Eid al-Adha celebration, both in managing the process of slaughtering sacrificial animals and the process of distributing sacrificial animal meat. This community service is an annual agenda at W.R. Supratman University, Surabaya. The implementation method is through a committee formation meeting, preparing an agenda, and proposing sacrificial animal slaughtering officers. Furthermore, providing assistance by being directly involved in the implementation of the slaughter and cutting of sacrificial animals and the distribution of sacrificial animal meat. The community service activity ends with monitoring and evaluation. The result is that with this assistance, the implementation of the slaughter and distribution of sacrificial animal meat in welcoming the 2024 Eid al-Adha holiday at the W.R. Supratman University Campus, Surabaya has become more orderly. The implementation of the slaughter of sacrificial animals and skinning of animals is carried out by experts, the chopping and weighing of meat is carried out proportionally, and the distribution of sacrificial meat is orderly, even and on target.